Knowledge, motivation and work culture on compliance in completing medical records at Ibnu Sina Hospital Makassar - Ningsi, Iin Widya; Hilmy, Mohamad Reza; Siswati, Siswati (Science Midwifery, 2024)
The importance of compliance in filling out medical records is a concern in the hospital service quality sector, because it has an impact on problems that often arise, namely filling in medical records, such as doctors' writing that is less specific and examinations that do not match the diagnosis. This situation has an impact on hospitals. This study aims to analyze the influence of knowledge, motivation and work culture on doctors' compliance in filling out medical records at Ibnu Sina Hospital Makassar. The type of research used is descriptive analysis, quantitative method, cross sectional design, to study the dynamics of correlation between risk and effect variables, using an approach, observation or data collection at the same time. Sample selection using purposive sampling technique by determining special characteristics according to the research objectives. The sample for this study was 70 doctors. The results of the research show that there is a correlation coefficient value of 0.276 on the knowledge variable, 0.390 on the motivation variable, 0.281 on the work culture variable and the results of multiple linear regression testing show an F-count value of 19.387 with a significant p value of 0.000 where there is at least 1 independent variable. influence on doctor's compliance simultaneously between the independent variable and the dependent variable. Therefore, knowledge, motivation and work culture have a significant influence on the doctor's compliance variable in filling out medical records.